2009
DOI: 10.1097/ta.0b013e31815edeb8
|View full text |Cite
|
Sign up to set email alerts
|

Distal Femoral Fixation: A Biomechanical Comparison of Trigen Retrograde Intramedullary (I.M.) Nail, Dynamic Condylar Screw (DCS), and Locking Compression Plate (LCP) Condylar Plate

Abstract: When considering micromotion and construct stiffness, the i.m. nail had statistically significant higher stiffness and significantly lower micromotion across the fracture gap with axial compression. Hence, the i.m. nail tested had the greatest stability for type 33-A fractures. However, the nail demonstrated the least amount of resistance to fatigue failure with type 33-C fractures, whereas the DCS did not fail with testing in any pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 48 publications
1
59
0
2
Order By: Relevance
“…[13][14][15] It is of interest that cadaveric studies have consistently showed that regardless of fracture pattern, retrograde intramedullary fixation with distal locking screws has demonstrated the highest resistance to fatigue, failure and resistance to both axial and torsional forces when compared to fixed angle devices. [16][17][18][19] In the line with the above, Pekmezci et al 15 confirmed that the new locking retrograde femoral nail (with more distal screw fixation) displayed better stiffness and fatigue life than locking plates and the mode of failure for the plate was invariably plate fatigue. Another surgical option that could be considered in these distal femoral fractures with fragmentation is acute endoprosthetic replacement.…”
Section: Introductionmentioning
confidence: 62%
“…[13][14][15] It is of interest that cadaveric studies have consistently showed that regardless of fracture pattern, retrograde intramedullary fixation with distal locking screws has demonstrated the highest resistance to fatigue, failure and resistance to both axial and torsional forces when compared to fixed angle devices. [16][17][18][19] In the line with the above, Pekmezci et al 15 confirmed that the new locking retrograde femoral nail (with more distal screw fixation) displayed better stiffness and fatigue life than locking plates and the mode of failure for the plate was invariably plate fatigue. Another surgical option that could be considered in these distal femoral fractures with fragmentation is acute endoprosthetic replacement.…”
Section: Introductionmentioning
confidence: 62%
“…5 However, in the recent years the results of internal fixation, even in the elderly patients, have generally been more favorable than conservative treatment with traction or cast bracing. 2,[6][7][8] Although distal femur replacing total knee replacement, angled blade plates, and other methods have been successfully used to treat distal femur fractures in the elderly patients, locked plating and intramedullary nailing remain the current standards of operative care. [9][10][11][12] Nevertheless, high rates of complications and mortalities continue to be reported in all methods of internal fixation for distal femur fractures in the elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…Distal femoral fractures continue to be a challenge for orthopedic surgeons. A number of treatment modalities for distal femur fractures have been reported in the literature, including dynamic condylar screw-plate (DCSPlates) (1)(2)(3)(4). Although many anatomic, morphologic, and radiologic studies have been carried out for femurs, as for all other bones of the skeletal system, we could not find any morphometric study useful for orthopedic surgeons wishing to understand DCS-Plate effects on the distal femur (5)(6)(7).…”
Section: Introductionmentioning
confidence: 38%